Percepción de los estudiantes que brindan atención odontológica en la clínica "Corona Gómez" frente a la atención de personas con discapacidad auditiva - Vaca Gavilánez, Fabiana Salomé (2025)
Introduction: It is estimated that between 1 and 3 out of every 1000 children suffer from hearing impairment, which can be congenital or acquired in childhood. This condition has a direct impact on their social life and, especially, on the quality of health care they receive. In addition, health personnel may have negative perceptions that impact the quality of care due to a lack of knowledge about the appropriate mechanisms to provide an optimal service. Objective: The purpose of this degree project was to determine the perception of students who provide dental care at the "Corona Gómez" clinic regarding the care of people with hearing impairment. Methodology: A 21-question survey was administered to 249 students in the final stages of the dentistry course to measure their perception of the care provided to these patients, categorised into three levels: good, neutral and bad. Results: A neutral perception of care for hearing impaired patients was obtained from the students surveyed, with a mean of 3.4426 points. In addition, some questions received responses below the mean, indicating levels of poor perception, while others obtained higher means, reflecting levels of good perception. Conclusion: According to the results obtained, it was verified that respondents have a neutral perception of care for hearing impaired patients. This shows the need to implement improvement actions, such as specific training or courses related to the treatment of patients with disabilities, which contribute to adequate care.